Familiarity and likings through implementation of Chinese traditional culture in digital product designs - Yang, Zongrui (2020)
Cultural innovation design is very reliable in making traditional culture up to date. With a population more than 1.4 billion people, China is blessed with many traditional cultural properties. However, in case of cultural properties, preserving is no longer hard but making it significant to the current and future generation is harder. Therefore, the purpose of this study is to understand the role of familiarity and liking in helping to improve the awareness of Chinese traditional culture among the Chinese people. Two surveys were conducted for this research, the first survey was to identify the most familiar and the most preferred cultural elements among the Chinese people. While the second survey validated the intention of the research. Using 5-points Likert scale, each participant were asked to rate the 10 product images based on their familiarity and liking level of preferences. Data were then analyzed using correlation analysis, ANOVA analysis, and descriptive analysis in SPSS. Results of the study indicated that, in survey 1, respondents preferred traditional color and nature patterns in palace culture. Through the data analysis for survey 2, respondents were indicated to prefer single color cultural elements, simple style with complete cultural elements. In addition, through the data analysis, this study confirmed that the design of new products with people's prefer cultural features will help them better understand their own culture and improve their cultural awareness.